The Effect of External Factors on Consumer Buying Behavior in the Cosmetics Market: Evidence from a Developing Country: Consumer Behavior in the Cosmetic Market - Ahmady, Razieh; Faraji, Hoda; Zeinali, Farahnaz; Sharifnia, Seyed Hesam; Yousefi, Nazila (Iranian Journal of Pharmaceutical Sciences, 2023)
Consumer decision-making plays a central role in some industries' success and failure, and scholars and practitioners have paid particular attention to the role of consumer behavior styles. This study aims to investigate the effects of product quality, product price, and brand marketing on consumer behavior in the cosmetics industry of a developing country. Data were collected from cosmetics consumers in selected pharmacies in Iran using structured questionnaires. Structural equation modeling was used to test the proposed research hypotheses. The results of this study show that product quality, price, and brand marketing directly influence consumers' behavior toward cosmetic products. Brand marketing was found to have the most significant influence on consumer buying behavior. These findings suggest that it is beneficial for companies to invest in their marketing strategies to gain a competitive advantage.